Investigating the Role of Serotonin in Methamphetamine Psychosis: Unaltered Behavioral Effects of Chronic Methamphetamine in 5-HT1A Knockout Mice - Jaehne, Emily J.; Ameti, Dzeneta; Paiva, Tehani; van den Buuse, Maarten (Frontiers in Psychiatry, 2017)
Methamphetamine (Meth) is a widely abused stimulant drug but this abuse is associated with an increased risk of developing psychosis. In addition to its well-known action on brain dopamine, Meth also affects serotonergic (5-HT) neurons. The aim of this study was to investigate this role in mice which lack one of the main serotonin receptors, the 5-HT1A receptor, which has been implicated in both schizophrenia and Meth-induced psychosis. Male and female wildtype (WT) or 5-HT1A knockout (KO) mice received daily treatment with increasing doses of methamphetamine from 6-9 weeks of age (1-4 mg/kg/day twice a day). At least two weeks after the last injection, the mice underwent a battery of behavioral tests focusing on psychosis-related behaviors, including Meth-induced hyperactivity, prepulse inhibition (PPI), social interaction, elevated plus maze (EPM) and Y-maze. Meth pre-treatment resulted in significantly increased hyperlocomotion in response to an acute Meth challenge but this effect was independent of genotype. Chronic Meth treatment resulted in decreased levels of anxiety in the EPM in both sexes, as well as increased startle responses in female mice only, again independent of genotype. 5-HT1A KO mice showed an increased locomotor response to acute Meth in both sexes, as well as increased PPI and decreased startle responses in female mice only, independent of Meth pre-treatment. In conclusion, the effects of chronic Meth appear unaffected by the absence of the 5-HT1A receptor. These results do not support a role of the 5-HT1A receptor in Meth-induced psychosis.